2022
DOI: 10.1038/s41598-022-07375-1
|View full text |Cite
|
Sign up to set email alerts
|

Targeted histological evaluation shows high incidence of actinomyces infection in medication-related osteonecrosis of the jaws

Abstract: Medication-Related Osteonecrosis of the Jaws (MRONJ) is a difficult-to-treat complication of the therapy of osteoporosis and some malignancies cured with bisphosphonates and antiresorptive drugs. The pathomechanism is unclear, but there is increasing observation that Actinomyces infection may play a role in its development and progression. The aim of our study was to demonstrate that histological examination using a validated triple staining procedure for Actinomyces bacteria strains can detect a high rate of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 53 publications
2
3
0
Order By: Relevance
“…In addition to these six mentioned phyla, Campylobacterota was also detected in all four groups in this study, consistent with previous research [10,38]. In previous studies, Actinomyces has been frequently detected in the oral microbiota of MRONJ patients [4,1,42]. Ceulaer et al [6] based on the modi ed Köhler hypothesis, comprehensively analyzed relevant literature and proposed that BRONJ is a type of actinomycotic osteomyelitis of the jaw.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In addition to these six mentioned phyla, Campylobacterota was also detected in all four groups in this study, consistent with previous research [10,38]. In previous studies, Actinomyces has been frequently detected in the oral microbiota of MRONJ patients [4,1,42]. Ceulaer et al [6] based on the modi ed Köhler hypothesis, comprehensively analyzed relevant literature and proposed that BRONJ is a type of actinomycotic osteomyelitis of the jaw.…”
Section: Discussionsupporting
confidence: 89%
“…Researches had indicated that the predominant phyla in MRONJ patients were Bacteroidetes, Firmicutes, Actinomycetes and Fusobacteria [10,24,8]. Additionally, Actinomyces could be found in almost all MRONJ patients [29,39,4]. In a study conducted by X Wei et al [38], 38 bacterial genera were detected in patients with BRONJ and other oral infections.…”
Section: Introductionmentioning
confidence: 99%
“…They can produce temporary bacteremia capable of causing microbial immune subversion that triggers systemic inflammation. The directed histological evaluation shows the high incidence of Actinomyces infection in drug-related osteonecrosis of the jaw [ 100 ], which was also observed in our study [ 35 ]. The critical role of bacterial infection in the pathogenesis of MRONJ can be justified by the decreased incidence in patients, after improved dental hygiene [ 100 , 101 , 102 , 103 ].…”
Section: Discussionsupporting
confidence: 82%
“…The directed histological evaluation shows the high incidence of Actinomyces infection in drug-related osteonecrosis of the jaw [100], which was also observed in our study [35]. The critical role of bacterial infection in the pathogenesis of MRONJ can be justified by the decreased incidence in patients, after improved dental hygiene [100][101][102][103]. Bisphosphonate-loaded bone is more susceptible to infections, not only because of the suppression of defense mechanisms, especially osteoclast activity and bone remodeling but also because the bisphosphonate-loaded bone is more prone to bacterial colonization [31].…”
Section: Discussionmentioning
confidence: 99%
“…CNS cases usually have delayed presentation; by that time, the lesion may have extensive fibrosis, which can impair the identification of sulfur granules. Recent reports highlight the role of targeted histological evaluation in increasing the detection of actinomycosis [ 34 ]. The advent of molecular techniques (PCR, 16S rRNA gene sequencing) allows the rapid identification of actinomycosis species.…”
Section: Discussionmentioning
confidence: 99%